OBSTETRIC CARE OF PREGNANT AND POST-PARTUM/BIRTH-GIVING WOMEN WITH COVID-19 - S. Radeva (Trakia Journal of Sciences)
Obstetric care, according to the regulations, is carried out in hospital treatment structures by qualified medical specialists. It requires a good organization that guarantees quality obstetric care in various conditions (emergency or scheduled admission) that will lead to the birth of a healthy and full-term newborn. Pregnant women are extremely susceptible to viral respiratory infections, including SARS-CoV-2. This is due to physiological and immunological changes that occur in the body during pregnancy. One of the serious problems of the pandemic that reached our country is the lack of sufficient and scientifically proven information. Research centers around the world are constantly analyzing what they have learned about the virus, the disease it causes, and all the accompanying factors. Infection with SARS-CoV-2 during pregnancy is not without risk for the future mother, who turns out to be more vulnerable to certain pathological complications. The consequences of infection with SARSCoV-2 in pregnant women pose many questions to doctors and researchers. Women's counseling plays an important role in proper behavior (to prepare the pregnant woman for the process of childbirth, to inform about all risks related to pregnancy and childbirth, to inform and conduct prevention of her behavior for the purpose of prevention), as well as all specialists, in case of COVID-19 diagnosis, for non-proliferation and prevention of complications.